Effects of telerehabilitation-based physical therapy for individuals with Parkinson’s disease: A systematic review protocol - Liliane Santos de Vasconcellos; Raíssa Souza Taveira; Luciana Protásio de Melo; Lorenna Raquel Dantas de Macêdo Borges; Lorenna Marques de Melo Santiago; Larissa Coutinho de Lucena; Tatiana Souza Ribeiro (PLoS ONE, 2026)
Introduction The use of telerehabilitation (TR) may increase in the next years due to the appreciation and acceptance of individuals with Parkinson’s Disease (PD). The objective of the present study is to evaluate the effects of physical therapy interventions administered remotely (TR) in individuals with PD. Methods and analysis This is a systematic review protocol in which randomized and quasi-randomized clinical trials of studies involving adults (≥ 18 years old) diagnosed with PD undergoing TR will be included. It is expected to provide evidence of the effects of TR in individuals with PD in terms of motor function; gait; balance; quality of life; number of falls; adverse effects; individual adherence to TR and fear of falling. Data will be synthesized using the Review Manager software. Registration details This systematic review protocol was registered on the Open Science Framework ( https://doi.org/10.17605/OSF.IO/ZVPX5-https://osf.io/zvpx5 ).